Public Debt and Economic Growth in Nigeria: Investigating the Optimal Threshold Level - Chile, Nzeh, Innocent (Asian Development Policy Review, 2020)
The current worrisome high debt situation in Nigeria amid falling revenue motivated this study. Using annual data spanning a period of 1981-2018 and under the framework of Autoregressive Distributed Lag (ARDL) bounds technique, the results of findings revealed that public debt contributes to the growth of the economy both in the short-run and in the long-run. However, after a certain threshold level, public debt leads to declining growth in both time horizons. The study also found the optimal threshold level of debt to be 40.2% in both the long-run and short-run. Also finding revealed that while trade openness contributes to GDP positively, both inflation and fiscal deficit adversely affect GDP. I therefore recommend that beyond using the debt-GDP ratio to decide when to borrow, regulatory authorities should consider other indices used to measure debt sustainability. Also, while there is need for diversification of the economy, a synergy should exist between monetary and fiscal authorities in order to fight inflation.